Onshore Skilled Migrant Engineers: Skills Wastage and Atrophy - Cameron, Roslyn; Joyce, D.; Wallace, M.; Kell, P. (National Institute of Labour Studies, 2013)
This article reports the survey findings from a research project exploring the use of skilled migration as a strategy for assisting in overcoming the pressing risks facing the Australian rail industry in workforce development. These risks are associated with an ageing workforce and skill shortages in engineering and technical areas. The data presented originate from a survey of skilled migrants in an employment program for skilled migrants in the Sydney metropolitan area and skilled migrant engineers in Victoria. The findings point to the potential, and yet untapped source of highly qualified professionals who could be targeted for recruitment by the rail industry. Of greater significance are the broader implications of the research in terms of engineering skills wastage and atrophy in a time when Australia cannot produce enough engineering professionals domestically to meet the demand. This is all set against a backdrop of global engineering shortages and fierce domestic competition for engineering skills made even more prominent with the second wave of the resources boom.